Pelatihan Self-Regulated Learning Pada Siswa Di SMP Negeri 10 Kupang - Wenyi Rohi, Enasely Mega; Margaretha, Dhiu; Lio, Stefanus; Marianus Un, Jefri Aprilius (Universitas Andi Djemma, 2025)
This community service program was conducted at SMP Negeri 10 Kupang which was attended by 26 students, the purpose of this service was to provide an important picture of self-regulated learning for students. Some of the main problems that are obstacles for students at SMP Negeri 10 Kupang are not being able to manage their study time well, preferring to play, not understanding the importance of independent learning. The implementation process goes through several stages, namely, delivering material, showing short film clips related to self-efficiency, training negative thoughts to positive ones in learning with worksheets, playing illustration games. The results of the Community Service activities show that after being given self-regulated learning training, it can help students in learning and understanding the importance of self-regulated learning.